A Mandate in the Shadow of Sanctions - A Study on the Legal and Practical Challenges of Representing a Sanctioned Party in International Arbitration - Kamishaj,Donjeta (2025)
Russia’s military aggression against Ukraine has prompted an extensive sanctions regime by the European Union (EU), which now plays a significant role in shaping the practice of international arbitration. These sanctions have not only made it more difficult to enforce international contracts, but have also placed lawyers in a difficult position, caught between legal obligations and ethical considerations. Given the rapidly changing nature of the sanction’s framework, even the permissibility of the representation of sanctioned parties has at times been questioned. For lawyers representing sanctioned Russian parties in international arbitration, the mandate demands the ability to navigate the effects that sanctions impose throughout the entire arbitration proceeding. The purpose of this thesis is to examine the legal and practical challenges that arise when legal counsel, subject to EU economic sanctions against Russia, represents a sanctioned Russian party in international arbitration. The study focuses specifically on Council Regulations 833/2014 and 269/2014, which were adopted in response to Russia’s annexation of Crimea in 2014 and further expanded following the full-scale invasion of Ukraine in 2022. The study explores how sanctions impact the effective conducting of international arbitration proceedings. It also examines their effect on issues like arbitrability, substantive assessment, and enforcement. Furthermore, it explores the extent to which these impacts introduce challenges that legal counsel must anticipate and address, when representing a sanctioned party in international arbitration. The study applies a combination of legal doctrinal and analytical methods, supported by comparative insights. The perspective of this thesis is the dual position of legal counsel, on one hand, as a guarantor of access to justice bound by professional ethics, and on the other, as a subject to the sanction’s regime, with an obligation to avoid breaches or circumvention. The research concludes that although legal representation of sanctioned parties is formally permitted, it presents several substantial challenges. These include complications relating to frozen assets, difficulties with bank transfers, reputational and ethical concerns, possible uncertainty regarding the scope of permitted legal advisory services and restrictions on enforceable claims. Furthermore, questions of arbitrability, substantive assessment and enforceability in sanction-related disputes shape the environment in which counsel must operate. The current framework leaves considerable space for uncertainty, particularly since multiple jurisdictions are involved. In summary, although some of these legal issues will ultimately need to be clarified by the Court of Justice of the European Union (CJEU), there is a clear need for more practical and accessible guidance from the European Commission, arbitral institutions, and bar associations, tailored to the realities of international arbitration proceedings. Furthermore, a mandate under sanctions requires an environment in which permissible services can be effectively performed.
Keywords: private law; EU law; international commercial arbitration; economic sanctions; legal counsel